OP0231 Differential Transcription Factor Binding Could Explain The Genetic Association of Ankylosing Spondylitis with Polymorphisms in The IL23R-IL12RB2 Intergenic Region. (15th July 2016) - Roberts, A.R.; Vecellio, M.; Chen, L.; Cohen, C.J.; Wordsworth, B.P.
Abstract : Background: Genome-wide association studies have revealed the polygenic nature of ankylosing spondylitis (AS). More than 60 genetic influences have been identified but most of these are non-coding sequences (1–3). Protection against AS is afforded by a loss of function mutation in the cytoplasmic tail of the IL23 receptor (IL23R), but there is also a second independent association in this region (2). Objectives: This study explores the functional basis for the second independent association between AS and single nucleotide polymorphisms (SNPs) in the IL23R - IL12RB2 intergenic region. Methods: We performed conditional analysis on genetic association data at IL23R and used epigenetic data on chromatin remodelling and transcription factor (TF) binding to identify the primary AS-associated SNP. Functional effects were tested in luciferase reporter assays in HEK293T cells and allele-specific TF binding was investigated by electrophoretic mobility gel shift assays. The involvement of candidate TFs in DNA binding was investigated by antibodies in these experiments. We measured mRNA expression levels of nearby genes in CD4+ T-cells and compared these between cases homozygous for the risk "A" allele and the protective "G" allele. The proportions of IL-17A+ and IFN-γ+ CD4+ T-cells were measured by FACS and also correlated to patient genotype. Results: Conditional analysis identified rs11209032 as the primary causal SNP within a putative enhancer between IL23R and IL12RB2 . Reduced luciferase activity was seen for the risk "A" allele (p<0.001), and reduced H3K4me1 methylation observed in CD4+ T-cells from "A/A" homozygotes (p=0.02). Nuclear extract binding to the risk "A" allele was decreased ∼3.5-fold compared to the protective allele (p<0.001). Reduced nuclear factor binding was observed when antibody to TWIST1 was included. The proportion of IFN-γ+ CD4+ T-cells was increased in "A/A" homozygotes (p=0.004), but neither IL23R nor IL12RB2 mRNA was affected. Conclusions: The rs11209032 SNP downstream of IL23R forms part of an enhancer, allelic variation of which may influence Th1-cell numbers. Homozygotes for the risk "A" allele have more Interferon gamma-secreting (Th1) cells compared to those with the protective "G" allele. Further work is necessary to explain how TWIST1 contributes to these important observations. References: Evans DM, Spencer CCA, Pointon JJ, et al. Interaction between ERAP1 and HLA-B27 in ankylosing spondylitis implicates peptide handling in the mechanism for HLA-B27 in disease susceptibility. Nat Genet 2011;43:761–7. Cortes A, Hadler J, Pointon JP, et al. Identification of multiple risk variants for ankylosing spondylitis through high-density genotyping of immune-related loci. Nat Genet 2013;45:730–40. Reveille JD, Sims A-M, Danoy P, et al. Genome-wide association study of ankylosing spondylitis identifies non-MHC susceptibility loci. Nat Genet 2010;42:123–7. Acknowledgement: This work was supported by the Arthritis Research UK (grant 20402, 20235, 19536, 18797, and 20796); and the NIHR comprehensive Biomedical Research Centre (immunity and inflammation theme A93081); NIHR Oxford Musculoskeletal Research Unit. Disclosure of Interest: None declared